FORMATION MECHANISM OF THE COMPLEX LANDSLIDE IN KRASNIK VILLAGE (CHERNIY CHEREMOSH RIVER BASIN) - IVANIK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Main factors of the landslide formation and the peculiarities of the landslide structure in Krasnik village (Ivano-Frankivska area) are defined. The landslide caused the transport objects deformations in this village. The complex mechanism of the landslide formation has been proved. Preventing activities for the hazards and the negative influence prevention has been proposed. This object could be used for the monitoring research of the landslide formation and classifications.